2001
DOI: 10.1111/j.1751-0813.2001.tb12010.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to Leptospira serovars in beef cattle in central Queensland

Abstract: These results are broadly similar to those of previous serological surveys. The data suggest that serovars other than hardjo, pomona and tarassovi, are unlikely to have a significant role in bovine subfertility and that cattle are unlikely to be a source of human infection with them in central Queensland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
5
10
0
Order By: Relevance
“…The younger pigs had relatively less reactants as compared to the middle to older age groups, probably because the older animals have lived longer in the environment, and thus, they have become more exposed to potential sources of infection. However, this study indicated that neither sex nor age had significant effects on the frequency of leptospira antibodies (P≥0.05), which is also in agreement with other studies (Black et al 2001).…”
Section: Discussionsupporting
confidence: 94%
“…The younger pigs had relatively less reactants as compared to the middle to older age groups, probably because the older animals have lived longer in the environment, and thus, they have become more exposed to potential sources of infection. However, this study indicated that neither sex nor age had significant effects on the frequency of leptospira antibodies (P≥0.05), which is also in agreement with other studies (Black et al 2001).…”
Section: Discussionsupporting
confidence: 94%
“…This is similar to that reported by Black et al (2001) where as age increased so did seropositivity. However, it differs to that reported in Turkey where age was not a significant factor (Aslantas and Ozdemir 2005).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous reports in cattle (Black et al 2001) and possums (Trichosurus vulpecula) (Eymann et al 2007). It is generally accepted that the serovar with the highest antibody titre likely represents the infective serovar (O'Keefe et al 2002), but this may not be true in every circumstance (Levett 2001).…”
Section: Discussionsupporting
confidence: 90%